Fabrication and characterization of superhydrophobic and superlipophilic silica nanofibers mats with excellent heat resistance - Gao S.; Watanabe H.; Nakane K.; Zhao K. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A kind of silica nanofibers (SNF) mats with superhydrophobicity and superlipophilicity as well as excellent heat resistance, had been prepared by modifying of 1, 1, 1, 3, 3, 3-hexamethyldisilazane on electrospun SNF mats. The effects of heat treatment time on properties of modified SNF mats were investigated by scanning electron microscopy, nitrogen absorption analysis, X-ray photoelectron spectroscopy, and contact angle measurement. With high specific surface area 240.1 m2/g, the optimal modified SNF mat approached water contact angle (WCA) 153.2° and fuel contact angle (FCA) 0°, furthermore, even after annealing by 450°C in air for 1h , WCA remained at 135.5° and FCA kept at 3.8°, which opened a new way to improve heat resistance of fuel-water filter paper.